An island flap based on the anterior branch of the superficial temporal artery for perioral defects - Raveendra Reddy Ganji; V. Bhattacharya; Adil Bashir Sheikh; Goyal Sunish (Indian Journal of Plastic Surgery)
Defects following excision of lesions in and around theoral commissure extending on either lip are not infrequent. A majority of them are malignant. Various local flaps have been described to correct these defects, but sometimes they may not be feasible. However, the advantage of single-stage reconstruction can still be achieved by using an island forehead flap based on the anterior branch of the superficial temporal artery. This is a versatile flap with a reliable blood supply. It is relatively less popular as it involves time-consuming dissection.Aims: We have modified the island forehead flap based on the anterior branch of the superficial temporal artery by designing the flap on the frontoparietal region based on the terminal course of the anterior branch of the superficial temporal artery. Materials and Methods: This flap was used in five cases of perioral defects involving both the upper and lower lips including the angle of the mouth. Conclusions: Small to moderate dimension full thickness perioral defects can thus be reconstructed effectively with this modified flap in a single stage. The functional and aesthetic results are gratifying with minimal donor site morbidity.